In Vivo Sustained Release of Peptide Vaccine Mediated by Dendritic Mesoporous Silica Nanocarriers - An, Weiteng; Defaus, Sira; Andreu, David; Rivera-Gil, Pilar (Frontiers in Immunology, 2021)
Mesoporous silica nanoparticles have drawn increasing attention as promising candidates in vaccine delivery. Previous studies evaluating silica-based vaccine delivery systems concentrated largely on macromolecular antigens such as inactivated whole viruses. In this study, we synthesized dendritic mesoporous silica nanoparticles (DMSNs) and we evaluated their effectiveness as delivery platforms for peptide-based subunit vaccines. We encapsulated and tested in vivo an earlier reported foot-and-mouth disease virus (FMDV) peptide vaccine (B2T). The B2T@DMSNs formulation contained the peptide vaccine and the DMSNs without further need of other compounds neither adjuvants and/or emulsions. We measured in vitro a sustained release up to 930h. B2T@DMSNs-57 and B2T@DMSNs-156 released 23.7% (135 µg) and 22.8% (132 µg) of the total B2T. The formation of a corona of serum proteins around the DMSNs increased the B2T release up to 61% (348 µg/mg) and 80% (464 µg/mg) for B2T@DMSNs-57 and B2T@DMSNs-156. In vitro results point out to a longer sustained release, assisted by the formation of a protein corona around DMSNs, compared to the reference formulation (i.e., B2T emulsified in Montanide). We further confirmed in vivo immunogenicity of B2T@DMSNs in a particle size-dependent manner. Since B2T@DMSNs elicited specific immune responses in mice with high IgG production like the reference B2T@MontanideTM, self-adjuvant properties of the DMSNs could be ascribed. Our results display DMSNs as efficacious nanocarriers for peptide-based vaccine administration.